Status of Elderly People in Chandragiri Municipality of Kathmandu - Parajuli, Keshab; Sijapati, Dipendra Bikram; Mishra, Manamaya (Historical Journal, 2024)
This paper examines the intricate connection between politics and journalism, highlighting the difficulties and effects of political influence on journalistic practices. The study shows, through a review of the, statement of problem, study of object and literature, that political beliefs have a major influence on media narratives, which frequently results in skewed reporting. The study is dependence of self-censorship, especially in authoritarian regimes. The crucial role that journalism plays in influencing public opinion and its consequencesfor democratic processes are also covered in this essay. It also draws attention to the difficulties that journalists encounter in politically delicate situations, such as censorship, physical threats, and legal constraints. The results highlight the necessity for journalistic independence and integrity to support democratic processes, as well as the dual role that media plays as a safeguard for democracy and a possible conduit for political influence. The study highlights the role that independent journalism plays in defending democratic norms in Nepal and notes the challenges that journalists confront in upholding impartiality and moral standards in the face of political polarization.